"Don't you care about the well‐being of your race?": African American couples discuss racial differences involving criticisms of other Black people. Issue 4 (5th July 2021) - Kelly, Shalonda; Kellman, Tara
Abstract: African American couples have unique racial stress and high relationship instability, although few studies have examined the role of racial stressors in their relationships. This qualitative study used grounded theory to examine 10 African American couples' disagreements about criticisms of other Black people. Each couple completed a standard couple problem‐solving task modified to focus solely on racial differences between the partners. Two models of couple relationships framed the approach; the general vulnerability‐stress‐adaptation model (Karney & Bradbury, Psychol . Bull ., 118, 1995, 3) was combined with a comprehensive race‐focused model (Bryant et al., J . Fam . Theory Rev ., 2, 2010, 157). The goal was to understand racial stress faced by African Americans, including its context, how and why it is stressful, how they cope, and its consequences in their relationship. A tentative model emerged, suggesting that some African Americans have early race‐related experiences that make them vulnerable to concerns about how Black people are seen by others. This may result in a unique minority status stressor that appears indicative of internalized stereotypes and may often include gendered criticisms of their partners. Partners seem to adapt by looking to other African Americans to take personal responsibility for their behavior and defending their racial group. Black male‐female gender role issues appear to emerge as a consequence of racial stress that also seems salient across all aspects of the model. Future studies can further examine culturally specific models involving African Americans' criticisms of other Black people and identify successful couple‐level strategies to overcome internalized oppression. Resumen: Las parejas afroestadounidenses tienen un estrés racial único y una gran inestabilidad en la relación, pero pocos estudios han analizado el papel que desempeñan los factores desencadenantes de estrés racial en sus relaciones. En este estudio cualitativo se utilizó la teoría fundamentada para analizar los desacuerdos de 10 parejas afroestadounidenses acerca de las críticas de otras personas de color. Cada pareja realizó una tarea estándar de resolución de problemas en la pareja modificada para centrarse únicamente en las diferencias raciales entre los integrantes de la pareja. El enfoque se enmarcó en dos modelos de relaciones de pareja. El modelo general de vulnerabilidad‐estrés‐adaptación (Karney & Bradbury, 1995) se combinó con un modelo integral centrado en la raza (Bryant et al., 2010). El objetivo fue comprender el estrés racial que enfrentan los afroestadounidenses, incluidos su contexto, cómo y por qué es estresante, cómo lo afrontan y sus consecuencias en su relación. Surgió un modelo tentativo, el cual indicó que algunos afroestadounidenses tienen experiencias tempranas relacionadas con la raza que los hacen vulnerables a las preocupaciones acerca de cómo otras personas ven a las personas de color. Esto puede generar un factor desencadenante de estrés único de las minorías que parece indicar estereotipos internalizados y con frecuencia puede incluir críticas marcadas por el género de sus parejas. Los integrantes de la pareja parecen adaptarse recurriendo a otros afroestadounidenses para que se responsabilicen personalmente de su conducta y defendiendo a su grupo racial. Aparentemente, los problemas de roles de género de los hombres y las mujeres de color surgen como consecuencia del estrés racial que también parece destacarse entre todos los aspectos del modelo. En futuros estudios se pueden analizar más profundamente modelos culturalmente específicos relacionados con las críticas de los afroestadounidenses a otras personas de color y reconocer estrategias satisfactorias a nivel de la pareja para superar la opresión internalizada. 摘要: 非洲裔美国夫妇有独特的种族压力和关系的不稳定性极高，尽管很少有研究调查种族压力因素在他们的关系中的作用。这项定性研究采用扎根理论，考察了10对非裔美国夫妇对其他黑人的批评意见分歧。每对情侣都完成了一项标准的情侣问题解决任务，该任务被修改为只关注伴侣之间的种族差异。两种伴侣关系模型为该方法提供了框架：将一般脆弱性‐应激‐适应模型(Karney & Bradbury, 1995)与综合比赛模型(Bryant et al.， 2010) 相结合。目的是了解非裔美国人面临的种族压力，包括它的背景，如何以及为什么会有压力，他们如何应对，以及在他们的关系中产生的后果。一种试探性的模式出现了，表明一些非洲裔美国人早期有与种族有关的经历，这使他们很容易受到其他人如何看待黑人的担忧的影响。这可能导致一种独特的少数族裔地位压力源，似乎表明内在化的刻板印象，并可能经常包括对其伴侣的性别批评。伴侣们似乎通过寻找其他非洲裔美国人来为自己的行为承担个人责任并捍卫自己的种族群体来适应。黑人男性和女性的性别角色问题似乎是种族压力的结果，这种压力似乎在模型的各个方面都很突出。未来的研究可以进一步调查非裔美国人批评其他黑人的文化特定模式，并确定克服内在化压迫的成功夫妇层面策略。